(3cJGH aj ZQjH GdMOjKs
(3ChdgG (B:s
(3jHOC HCKfGA MQa GdCda (B( (3hSWgG Ydi Jd Ke jLdS YdGe Ydi CMO WQajgG bhdg CShO CaLL GdCUeYi GdaLL (B: (3JHGYO eG Hjf GdaNPjf s
(3BNQgG (B:s
(3hGdabe (B: (3GdMfc Ke MQa GdjGA hgh BNQ GdOjhGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs